Compositional-cultural evolutions as variations of Malay architectural and constructional vocabulary- a review - Jahn Kassim, Puteri Shireen; Ali, Maisarah; Mohd Nawawi, Norwina; Mustafa, Muhammad Hadi (2018)
Malay traditional architectural and construction vocabulary and its terminologies have arisen from centuries of use and evolution from local folk and vernacular structures, artisanal traditions and methods. While challenges in universalising these terms are faced due to the extreme diversity of the Malay archipelago region and its cultural and ethnic variations, there are also acute challenges that are faced due to rapid modernity in this region, from which past vernacular terminologies can no longer cope with the complexity and hybridity of architectural language. The Malay societies and states since the 1400s, Malay architecture and its elements have encountered syncretism and absorption of external influences and ideas. The paper attempts a review of the relationship between Malay architecture and its language used to describe its elements as a social practice. There is also a current need to find adequate terms and words used to describe Malay architecture in English, regarding composition and aesthetics are key to the infusion of identity in current public buildings. These may have somehow contributed to its lack of uptake in the modern building as its descriptions and representation need to respond to urbanised development and modern growth. As one debate about Malay architecture, one must describe it more than merely past timber forms, and techniques, but modernised elements rooted vernacular concepts and past practices ―as these must now directly and reflect the ways Malays have been thinking and living in urban spaces and buildings. This paper attempts to report on the effort to relook at the vocabulary of Malay architecture, its compositional potentials, weaknesses and strengths, local and regional variations. It attempts and aims towards a thorough examination of the complex relationship between architecture and language as intricate social practices. A vocabulary of key terms are investigated; including links between language and CAD measured drawing; and the need for universal semantic elements that go beyond its vernacular or folk traditions.